Efektifitas Edukasi Berbasis Pangan Lokal Jantung Pisang Terhadap Peningkatan Pengetahuan Ibu Tentang Produksi ASI - Hasriati, Wa Ode; Wahid, Wa Ode Putri Agustina; Harnaningsi, Harnaningsi; Zulaeha, Wa Ode (Madu : Jurnal Kesehatan, 2025)
The incidence of stunting in Boneatiro Village is quite high, with 36 reported cases. One of the contributing factors to stunting in the village is the low rate of exclusive breastfeeding, which remains below 50%. Optimal breast milk production is crucial to the success of exclusive breastfeeding during the first six months of an infant’s life. One effort to increase breast milk production is through the consumption of natural lactagogue foods, such as banana blossoms. This study aims to determine the effectiveness of local food–based education using banana blossoms in improving maternal knowledge in Boneatiro Village in 2025. This research is a quantitative study with a pre-experimental design using a one-group pretest–posttest approach. This method aims to measure changes in maternal knowledge before and after receiving nutrition education based on local food (banana blossoms), with a sample of 100 women of reproductive age selected using purposive sampling. The results, analyzed using the Wilcoxon test, showed a p-value of 0.002 (<0.05), indicating a significant difference in maternal knowledge before and after the education intervention. It is recommended that future studies involve a larger population, assess the impact of education on dietary behavior, and monitor the long-term effects on nutritional status and child growth.